Trigonometry (11th Edition) Clone

Published by Pearson
ISBN 10: 978-0-13-421743-7
ISBN 13: 978-0-13421-743-7

Appendix C - Functions - Page 437: 41



Work Step by Step

We are given that $g(x)=-x^{2}+4x+1$. We can plug the given value into the equation and evaluate. $g(\frac{1}{2})=-(\frac{1}{2})^{2}+4(\frac{1}{2})+1=-(\frac{1}{4})+2+1=-\frac{1}{4}+2+1=-\frac{1}{4}+\frac{8}{4}+\frac{4}{4}=\frac{-1+8+4}{4}=\frac{11}{4}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.